2014
DOI: 10.3349/ymj.2014.55.2.459
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Commercial Glycoprotein Enzyme-Linked Immunosorbent Assay for Measuring Vaccine Immunity to Varicella

Abstract: PurposeTo evaluate a recently marketed commercial glycoprotein enzyme-linked immunosorbent assay (gpEIA) kit, the VaccZyme™ VZV gpEIA, for measuring the immunity of varicella-vaccinated children.Materials and MethodsWe investigated the accuracy and reproducibility of the VaccZyme™ VZV gpEIA kit for the detection of antibodies to VZV. We also examined the sensitivity, specificity, and correlation between antibody titers calculated with gpEIA versus fluorescent antibody to membrane antigen (FAMA) by using sera o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The FAMA assay was performed using live cells, as described previously in New York (1) and Korea (13). The ELISA used for the serum samples from South Korea was performed using the VaccZyme VZV glycoprotein enzyme immunoassay (gpEIA) kit (The Binding Site, United Kingdom); an antibody titer of Ͻ50 mIU/ml was interpreted as seronegative (13). The ELISA used for the serum samples from the NIH was performed using the Trinity Biotech Captia VZV IgG kit, which uses inactivated VZV antigen.…”
Section: Methodsmentioning
confidence: 99%
“…The FAMA assay was performed using live cells, as described previously in New York (1) and Korea (13). The ELISA used for the serum samples from South Korea was performed using the VaccZyme VZV glycoprotein enzyme immunoassay (gpEIA) kit (The Binding Site, United Kingdom); an antibody titer of Ͻ50 mIU/ml was interpreted as seronegative (13). The ELISA used for the serum samples from the NIH was performed using the Trinity Biotech Captia VZV IgG kit, which uses inactivated VZV antigen.…”
Section: Methodsmentioning
confidence: 99%
“…Because VZV serological tests are performed to determine susceptibility to VZV infection, the cutoff value is important. A titer of <1:4 serum dilution and a gpEIA <50 mIU/ml have been used as negative cutoff values [1,10]. gE FAMA titration revealed that FAMA negative at 1:8 was lower than gpEIA 50 mIU/ml.…”
Section: Discussionmentioning
confidence: 99%
“…For the FAMA test, cells were infected either with VZV or plasmid. Basically, we performed the classic FAMA test according to William's method with some modifications [10,17]. For gE FAMA, HEK293T cells were transfected with plasmid encoding VZV gE.…”
Section: Fama Testmentioning
confidence: 99%
“…However, ELISA may be less useful in the future when a greater portion of the population has been vaccinated. ELISA had lower sensitivity compared to the FAMA test in determining protective immunity against VZV, especially in vaccinees [ 25 27 , 37 ], and thus the false-negative rate of ELISA may increase with the growing vaccinated population.…”
Section: Discussionmentioning
confidence: 99%